2018
DOI: 10.1177/0018720818794526
|View full text |Cite
|
Sign up to set email alerts
|

Angle of Camera View Influences Resumption Lag in a Visual-Motor Task

Abstract: Training for laparoscopic surgery should include interruptions to allow surgeons to practice resuming a surgery-related task after an interruption and consequently shorten the time needed to resume the surgery-related task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Since these systems provide additional functions beneficial for road safety (e.g., increased field of view, monitors positioned closer to the driver’s eye point, image augmentation), the increased acceptance could increase road safety indirectly. Positive effects of a higher perspective on orientation and localization have been observed in visual-motor tasks (Lodinger & DeLucia, 2019; Ustinova et al, 2010) and indirect viewing systems (Bao et al, 2013; van Erp & Padmos, 2003). Moreover, Viputsakul et al (2020) observed improved localization performance with a digital bird’s-eye view mirror.…”
Section: Discussionmentioning
confidence: 99%
“…Since these systems provide additional functions beneficial for road safety (e.g., increased field of view, monitors positioned closer to the driver’s eye point, image augmentation), the increased acceptance could increase road safety indirectly. Positive effects of a higher perspective on orientation and localization have been observed in visual-motor tasks (Lodinger & DeLucia, 2019; Ustinova et al, 2010) and indirect viewing systems (Bao et al, 2013; van Erp & Padmos, 2003). Moreover, Viputsakul et al (2020) observed improved localization performance with a digital bird’s-eye view mirror.…”
Section: Discussionmentioning
confidence: 99%